Pengaruh model latihan tendangan dollyo chagi menggunakan elastis power terhadap daya ledak otot tungkai dan frekuensi tendangan pada olahraga taekwondo di dojang cendrawasih sumbawa - Yani Yuliana; Muhamad Salabi; Aminullah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
This study aims to determine the effect of the dollyo chagi kick training model using elastic power on the explosive power of the leg muscles and the frequency of kicks in taekwondo sports in Cendrawasih Sumbawa. This study is a pre-experimental design study. The data collection technique used in this study used, data collection in this study by conducting observations and using the standing long jump test technique given to the experimental group, and documentation. The analysis technique used is quantitative descriptive analysis. The results of the study based on the results of the analysis using the Paired Sample T Test, it is known that the male training participants obtained a t-count of -8.113 with a significance value of 0.000 and the female training participants obtained a t-count of -6.786 with a significance value of 0.000. The significance value (p) is smaller than the significance level of 0.05 (p <α = 0.05), then H0 is rejected and Ha is accepted. This means that there is a significant effect on the average value of the explosive power of the leg muscles between before and after being treated. Thus, the dollyo chagi kick training program using elastic power can significantly increase the explosive power of the leg muscles.